STRATEGI KOMUNIKASI PESAMARAN EJJI COFFEE CORNER CABANG PURIMAS SURABAYA DALAM MENINGKATKAN KONSUMEN DI MASA PANDEMI COVID-19 - Fakri Reza K.; Saifuddin Zuhri (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
This research is based on how the marketing communication strategy of Ejji Coffee Corner Surabaya in increasing the number of consumers in times of pandemic. In this study, the researcher uses qualitative research methods, which are research that seeks to interpret and interpret an event or occurrence regarding the interaction of human behavior patterns in certain situations or conditions according to the researcher's own perception. Through the process of analysis and discussion of marketing communication strategies conducted by Ejji Coffee Corner Purimas branch in increasing consumers during this pandemic, the researcher can draw the conclusion that in implementing the marketing communication strategy, it can be seen from several points of the marketing communication mix, namely the promotion mix carried out by Ejji Coffee Corner, there are several elements in this promotion mix , including advertising, personal selling, sales promotion, publicity and franchise (partnership). From the elements in the promotion mix , a successful marketing strategy was carried out, especially for Ejji Coffee Corner Purimas branch, namely through personal selling and publications, in the application of personal selling they offered their products by mouth word of(mouth to mouth), while in the publication strategy Ejji Coffee Corner does marketing with a focus on digital marketing with the media used, namely Instagram. In determining the marketing strategy, consider the strengths and opportunities that are owned. In connection with this matter, we continue to look at the factors of weakness and threats, lest strengths and opportunities turn into big threats for Ejji Coffee Corner and during the current Covid-19 pandemic, it is better to prioritize payments using e-money or e-wallet, to minimize physical contact with customers together to break the chain of the spread of Covid-19. Keywords: Marketing Communication Strategy, Digital Marketing, Promotion Mix